TI_GERICHTE 35.2024.52 vom 2. September 2024 , Discussa l'esistenza di un infortunio, rispettivamente di una lesione parificata - TI Tribunale d'appello (2024)
Discussa l'esistenza di un infortunio, rispettivamente di una lesione parificata